Análise bioética da propaganda e publicidade de medicamentos Bioethical analysis of drugs advertisement and publicity - Maria José Delgado Fagundes (Ciência & Saúde Coletiva, 2007)
Sob a perspectiva da "ética da proteção" e da "bioética de intervenção", a pesquisa analisa a influência das peças publicitárias de medicamentos veiculadas à classe médica na prescrição de medicamentos. Estuda, ainda, a qualidade das informações nas propagandas de medicamentos de venda sob prescrição, antes e depois da Resolução da Diretoria Colegiada da Anvisa - RDC 102/2000, que regulamenta a propaganda de medicamentos no país, bem como discute o papel regulador do Estado na área. Primeiramente, foram entrevistados 50 médicos de Brasília, a fim de examinar como percebem os efeitos da propaganda sobre sua atividade profissional. Em seguida, foram avaliadas 10 peças publicitárias, 5 veiculadas antes e 5 depois da RDC 102/2000. Os resultados permitiram concluir que: a) 98% dos médicos recebem visitas regulares de representantes comerciais; b) 86% recebem brindes; c) 68% crêem na influência direta da propaganda sobre a prescrição; d) 14% disseram prescrever medicamentos em função do recebimento de prêmios; e) 68% acreditam existir inverdades nas informações das peças publicitárias; f) antes da RDC, as informações (contra-indicações, indicações, precauções, cuidados e advertência) nas propagandas representava 28% dos casos; após a RDC, foram encontradas informações em 79% dos casos. This study investigates how advertising campaigns for drugs influence drug prescription practices among physicians from a point of view of "protection ethics" and of "intervention bioethics". It also analyzes information quality in advertisements for prescription drugs before and after the ANVISA (National Agency for Sanitary Protection) RDC 102/200 Resolution wich regulates drugs advertising as well as discusses the regulating role of the state in this area. A first approach was to interview 50 physicians in Brasília/DF (25 general physicians and 25 surgeons) in order to examine how they perceive the effects of advertisement on their professional activities. A second approach was to study 10 publicity pieces, five from before and five from after the RDC Resolution. The results showed that: a) 98% of phsicians are visited by sales representatives on a regular basis; b) 86% of physicians receive gifts during these visits; c) 68% beleive that advertising strongly influences prescription practices; d) 14% related prescription practices to the receival of rewards; e) 68% beleive that information contained in advertisements is unreliable; f) before the RDC Resolution, 28% of advertisements had adequate information content (counter-indications, indications precautions, warnings, and adverse reactions); after the RDC Resolution, that number grew to 79%.